2015
DOI: 10.1002/app.42577
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon black and nanoclay on mechanical and thermal properties of ABS–PANI/ABS–PPy blends

Abstract: Acrylonitrile butadiene styrene (ABS)-polyaniline (PANI) and ABS-polypyrrole (PPy) blends exhibit poor mechanical and thermal properties due to their weak interfacial adhesion and inhomogeneous mixing. The properties have been improved by addition of carbon black (CB) and nanoclay (NC). Composites are prepared by mixing CB and NC with ABS-PANI and ABS-PPY blends. The morphology and crystalline characteristics are studied using field emission scanning electron spectroscopy (FESEM) and X-ray diffraction, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The reduction of the stiffening effect of fillers resulted in lower E’ value. When the infill density increased, a close raster and deposited fibers were generated, which led to a denser structure and improvement in E’ of the printed parts [ 29 ]. Rectilinear samples showed a slightly lower storage modulus value at all temperatures below glass transition temperature, Tg, compared to line samples, due to less stiff structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction of the stiffening effect of fillers resulted in lower E’ value. When the infill density increased, a close raster and deposited fibers were generated, which led to a denser structure and improvement in E’ of the printed parts [ 29 ]. Rectilinear samples showed a slightly lower storage modulus value at all temperatures below glass transition temperature, Tg, compared to line samples, due to less stiff structure.…”
Section: Resultsmentioning
confidence: 99%
“…No significant impact was observed on the Tg for printing pattern and infill density change. Increasing Tan δ means the material has more energy dissipation potential, whereas decreasing Tan δ means when load is applied, the material has more potential to store the load, rather than dissipating it [ 28 , 29 ]. Results in Figure 8 e showed Tan δ decreased with infill density.…”
Section: Resultsmentioning
confidence: 99%
“…[ 329 ] Peighambardoust et al [ 330 ] prepared a PA6‐matrix composite with in situ polymerized PPy/MMT and observed conductivity of 1.66 × 10 −4 S cm −1 at 25 wt% PPy and 5 wt% MMT. Debnath et al [ 331 ] melt blended CB and nanoclays to improve the mechanical strength of ABS/PPy and ABS/PANI blends. As CB and nanoclay fillers worked as a heat absorber, the processability of ABS/ PPy and ABS/PANI blends was improved, but it is unclear what the effect was on electrical conductivity.…”
Section: Conductive Polymersmentioning
confidence: 99%
“…Wang et al also reported on the electro‐rheological properties of polyaniline nanofiber/kaolinite hybrid nanocomposite prepared by rapidly mixed in‐situ polymerization . Similarly, Debnath et al also described the effect of carbon black and nanoclay on mechanical and thermal properties of ABS‐PANI/ABS‐PPy blends . Despite of such superior properties, fundamental understanding has yet to emerge with the prospects of development of nanostructured material with improved polymer/silicate interface.…”
Section: Introductionmentioning
confidence: 99%
“…[27] Similarly, Debnath et al also described the effect of carbon black and nanoclay on mechanical and thermal properties of ABS-PANI/ABS-PPy blends. [28] Despite of such superior properties, fundamental understanding has yet to emerge with the prospects of development of nanostructured material with improved polymer/silicate interface.…”
Section: Introductionmentioning
confidence: 99%